2012
DOI: 10.1186/1741-7007-10-40
|View full text |Cite
|
Sign up to set email alerts
|

Macondo crude oil from the Deepwater Horizon oil spill disrupts specific developmental processes during zebrafish embryogenesis

Abstract: BackgroundThe Deepwater Horizon disaster was the largest marine oil spill in history, and total vertical exposure of oil to the water column suggests it could impact an enormous diversity of ecosystems. The most vulnerable organisms are those encountering these pollutants during their early life stages. Water-soluble components of crude oil and specific polycyclic aromatic hydrocarbons have been shown to cause defects in cardiovascular and craniofacial development in a variety of teleost species, but the devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 121 publications
1
47
0
Order By: Relevance
“…The above crude oil cardiotoxicity syndrome has been extensively characterized in zebrafish embryos exposed to several geologically distinct oils (17,21,23,30,31), including the Mississippi Canyon 252 (MC252) crude oil released from the blown out Deepwater Horizon wellhead (20,32). Similar effects have been reported for temperate marine and anadromous species, such as Pacific herring (19,26,27,33) and pink salmon (34,35), following exposure to Alaska North Slope crude oil.…”
Section: Significancementioning
confidence: 79%
“…The above crude oil cardiotoxicity syndrome has been extensively characterized in zebrafish embryos exposed to several geologically distinct oils (17,21,23,30,31), including the Mississippi Canyon 252 (MC252) crude oil released from the blown out Deepwater Horizon wellhead (20,32). Similar effects have been reported for temperate marine and anadromous species, such as Pacific herring (19,26,27,33) and pink salmon (34,35), following exposure to Alaska North Slope crude oil.…”
Section: Significancementioning
confidence: 79%
“…In seabird colonies, successful annual reproduction was still 70% lower than historical rates, 5 yr after the Prestige oil spill (Barros et al 2014). Reproductive and early developmental effects have also been documented in fish species exposed to oil from the Exxon Valdez, Prestige, and Deep water Horizon spills (Hawkes & Stehr 1982, Kocan et al 1996, Bilbao et al 2010, de Soysa et al 2012, Kawa guchi et al 2012, Whitehead et al 2012, Turner et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that WAF 10W-40 motor oil affected the early life stage embryos of zebrafish a dose-dependent manner. Embryotoxic effects such as weak pigmentation, tail defects, and reduced heartbeat rate were reported in embryos exposed to 15, 33 and 50 v/v crude oil during 96 h (Pauka et al, 2011). De Soysa et al (2012 indicated that the Maconda crude oil WAF caused a various defects in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%